The role of non-starter bacterial consortia in mould-ripened cheese - Yunita, Dewi (2016)
Stichelton is a blue-veined raw milk cheese which is made following the Stilton cheese making process. In a previous study, a preliminary examination of its microflora during production was examined by traditional culture methods and initial PCR DGGE profiling. The aim of this study was to complete the profiling of Stichelton cheese and examine the contribution of its microbiota components to product characteristics.